BS EN 17415-2. District cooling pipes. Bonded single pipe systems for directly buried cold water networks. Part 2. Factory made fitting assemblies of steel or plastic service pipe, polyurethane thermal insulation and a casing of polyethylene (23rd July 2020) - British Standards Institution,
No abstract available